Implementation of Islamic Human Resource Management in Islamic Boarding Schools: Case Study in Modern Islamic Boarding Schools - Aep Tata Suryana (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to examine the strategy of HRM development in modern Islamic boarding schools based on Islamic principles. This study uses a qualitative approach by collecting data from various sources such as the results of previous studies. The collected data will be analyzed thematically to identify patterns and main themes relevant to the research objectives. The results of the study indicate that the implementation of HRM based on Islamic principles can improve individual and organizational performance in Islamic boarding schools. The principles of fairness and transparency in recruitment and promotion, the welfare of teachers and staff, and the enforcement of ethics and integrity are key factors in the success of HRM. Cultural and traditional challenges can be overcome by aligning conventional values ”‹”‹with modern management principles through education and dialogue. Limited resources can be overcome with creative and collaborative solutions, such as cooperation with non-profit organizations and the private sector. Adapting to technological change requires investment in infrastructure and training, as well as cultivating innovation throughout the organization. With the right strategy, Islamic boarding schools can implement effective human resource management that follows Islamic values, so that they can produce competent and noble graduates.